eCM 2008
DOI: 10.22203/ecm.v015a02
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS-5: The story so far

Abstract: The recent discovery of ADAMTS-5 as the major aggrecanase in mouse cartilage came as a surprise. A great deal of research had focused on ADAMTS-4 and much less was known about the regulation, expression and activity of ADAMTS-5. Two years on, it is still not clear whether ADAMTS-4 or ADAMTS-5 is the major aggrecanase in human cartilage. On the one hand there are in vitro studies using siRNA, neutralising antibodies and immunoprecipitation with anti-ADAMTS antibodies that suggest a significant role for ADAMTS-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 150 publications
5
84
0
1
Order By: Relevance
“…In general, ADAMTS-5 is constitutively expressed in human chondrocytes and synovial fibroblasts, whereas ADAMTS-4 expression is induced by proinflammatory cytokines (Fosang et al, 2008). The active forms of ADAMTS-4 were increased in synovial fluid samples from patients with active Lyme arthritis (Behera et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In general, ADAMTS-5 is constitutively expressed in human chondrocytes and synovial fibroblasts, whereas ADAMTS-4 expression is induced by proinflammatory cytokines (Fosang et al, 2008). The active forms of ADAMTS-4 were increased in synovial fluid samples from patients with active Lyme arthritis (Behera et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Aggrecan turnover within the extracellular matrix occurs due to the enhanced activity of endoproteinases such as a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) 4 (3, 4) and 5 (5,6) as well as other matrix metalloproteinases (MMPs) (7)(8)(9)(10)(11). In addition to aggrecan, a significant loss of hyaluronan (HA) is also observed in human OA cartilage as compared with normal human cartilage (12,13).…”
mentioning
confidence: 99%
“…TIMP-3 is the major endogenous inhibitor of aggrecanases known to date (for review, see ref. 5), and Timp3 -/-mice (age Ն6 months) exhibit cartilage destruction (14). In the study by Chia et al, no effects on Timp3 expression were observed under any conditions, although Timp1 levels were increased following surgery in either WT or Fgf2 -/-mice.…”
Section: Jelena Gavrilovicmentioning
confidence: 94%
“…5). Elegant studies in mouse models of arthritis have revealed that ADAMTS-5 is the key enzyme in aggrecan breakdown in this context (6,7).…”
Section: Jelena Gavrilovicmentioning
confidence: 99%